The relationship of leadership styles and competencies on job satisfaction of lecturers in Polytechnic Kota Kinabalu/ Jacquelyne Ekot - Ekot, Jacquelyne (2013)
It is undoubtly that Polytechnic transformation was important to achieve Malaysia's aspiration to become a progressive backbone toward its vision and long terms goals, especially to quantify knowledge-based goals. In order to supply a world class manpower, the lecturers in Polytechnic Kota Kinabalu (PKK) need to be productive and excellent in delivering knowledge to students. Thus, in the process of achieving the vision of Polytechnic, this study will focus on the i1npact of leadership styles and competencies of the Director of Polytechnic Kota Kinabalu (PKI() on job satisfaction among lecturers. The common problem among the teaching staff in Polytehcnic is the feeling of dissastisfaction towards the leadership styles of the leader as well as the leader's level of competencies .To this end, 199 lecturers were selected randomly from different departments to participate in the study. Leadership styles was measured by the 20-itein Leadership Style Questionnaire developed by Northouse (2001). Leaders' competencies were measured by the Eight Universal Management and Leadership Competencies in 18 Skill Sets developed by the Profile Service Centre. Job satisfaction was measured by using the 5-itein questionnaire developed by Brayfield and Rothe (1951 ). The result of the study shows that there is no correlation between leadership styles ( M = 2.95, SD = 1.11) and lecturers' job satisfaction ( M = 3.13, SD= 1.22) in Polytechnic Kota Kinabalu. The result reveals that there is significance between leadership competencies ( M = 2.76, SD= 0.95) and leadership styles ( M = 3.13, SD= 1.22) of Director of Polytechnic Kota Kinabalu. Fro111 the result, it presents that there is no significance between leader's cornpetencies ( M = 2. 76, SD = 0.95) and lecturers' job satisfaction ( M = 3.13, SD = 1.22) in Polytechnic Kota Kinabalu. The limitations of this study and the recommendations for future research are also discussed.